2016
DOI: 10.1186/s13046-016-0378-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SALL4 reduces tumorigenicity involving epithelial-mesenchymal transition via Wnt/β-catenin pathway in esophageal squamous cell carcinoma

Abstract: BackgroundGrowing evidence suggests that SALL4 plays a vital role in tumor progression and metastasis. However, the molecular mechanism of SALL4 promoting esophageal squamous cell carcinoma (ESCC) remains to be elucidated.MethodsThe gene and protein expression profiles- were examined by using quantitative real-time PCR, immunohistochemistry and western blotting. Small hairpin RNA was used to evaluate the role of SALL4 both in cell lines and in animal models. Cell proliferation, apoptosis and invasion were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 46 publications
8
84
0
Order By: Relevance
“…PKCζ affects β‐catenin stability, further affecting stem cell function . The Wnt/β‐catenin pathway plays an important role in tumor cell EMT and stemness; such report is consistent with our results from KEGG pathway analysis based on the differential genes between cPLA2α KD and KD/SCR CSCs and from mass spectrometry analysis. Many β‐catenin molecules bound to the cytomembrane with E‐cadherin, and less nuclear translocation of β‐catenin occurred when PKCζ was knocked down regulated by cPLA2α inhibition, leading to increased E‐cadherin‐mediated cell‐to‐cell adhesion and blockage of EMT and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…PKCζ affects β‐catenin stability, further affecting stem cell function . The Wnt/β‐catenin pathway plays an important role in tumor cell EMT and stemness; such report is consistent with our results from KEGG pathway analysis based on the differential genes between cPLA2α KD and KD/SCR CSCs and from mass spectrometry analysis. Many β‐catenin molecules bound to the cytomembrane with E‐cadherin, and less nuclear translocation of β‐catenin occurred when PKCζ was knocked down regulated by cPLA2α inhibition, leading to increased E‐cadherin‐mediated cell‐to‐cell adhesion and blockage of EMT and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…It had been reported that SALL4 induced myelodysplastic syndrome and acute myeloid leukemia by activating the Wnt/β‐catenin signaling pathway . In esophageal squamous cell carcinoma, inhibition of SALL4 reduces the tumorigenicity via the Wnt/β‐catenin signaling pathway . We investigated whether the function of SALL4 in cervical cancer cells was also associated with the Wnt/β‐catenin signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the shRNA knockdown of CHI3L1, a gene identified for etoposide and cisplatin response in every tissue, has been shown to sensitize glioma cells to these two drugs, while its overexpression reduced their sensitivity [41]. As another example, the knockdown of SALL4 (identified in all tissues) in cancer cell lines has been shown to increase the sensitivity of lung cancer cells [42] and esophageal squamous cell carcinoma cells [43] to cisplatin. Supplementary Table S7 summarizes some of the evidence we curated from literature for the role of different genes identified by TG-LASSO in all tissue types for cisplatin, as an illustration.…”
Section: Resultsmentioning
confidence: 99%